Od prenove poslovanja k upravljanju delovnih procesov - Leben, Anamarija (Uporabna informatika (Ljubljana), 1997)
There are two concepts that have appeared in the field of business informaticsin the last few years: Business process Reingeneering and Workflow Management. The last one, which actually represents a technical sight of reengeneering, a quite few in our environment. This article therefore focuses on bacis concepts of Workflow Management. In addition to this concept WorkflowManagement Systems are described.
Keywords: delovni procesi; informatika; poslovanje podjetja; upravljanje